Pengaruh Aktivitas Bermain Game Online terhadap Akhlak dan Motivasi Belajar Siswa SMA Negeri di Kabupaten Penajam Paser Utara - Wahid Waham; M. Ajie Faisal Muttaqin Z.A; Rifka Novi Utami; Andri Wardana Putra; Sherly Susilo Rahayu; Sirajuddin; Siti Aisyah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
This research is motivated by the rise of online game playing activity of student SMA Negeri in Kabupaten Penajam Paser Utara, which has an effect on moral change and a decrease in students’ study motivation who actively plays online games. This study aims to find out how the activity of playing online games, the morals, and the students’study motivation, how much the influence of online games playing activity on morals and students’ study motivation, and how much the influence of online game playing activity on morals and students’ study motivation simultaneosly. The type of this research is quantitative research, with data collection techniques used the form of questionnaires and documentation. The data analysis technique is simple linear regression and multiple linear regression. The population is all students of class X of SMAN 3, SMAN 4 and SMAN 5 of Kabupaten Penajam Paser Utara, totaling 467 people. The sample amounted to 94 people with purposive sampling technique. The research result show that : (1) the online game playing activity of students is a good with a value of μ = 46 (μ = X ˃ 51 ), (2) the morals of studens is so good with a value of μ = 52 (μ = Y1 ˃ 51 ), (3) Students’ study motivationis is a good with a value μ = 49 (μ = Y2 ˃ 51 ). (4) The value of rx_Y1 is 0,615, with a strong intensity and t_test = 7,487 > t_table = 1,66159, so Ha is accepted which means that the online game playing activity has a significant effect on the moral. The value of the coefficient of determination proves that online game playing activity has an effect 37,9% on the students’ moral and 62,1% is influenced by other variables. (5) The value of rx_Y2 is 0,619, with a strong influence and t_test =7,562 > 1,66159, so Ha is accepted which means that the online game playing activity has a significant effect on the motivation of study. The value of the coefficient of determination proves that online game playing activity has an effect 38,3% on the motivation of study and 61,7% is influenced by other variables. (6) Furthermore, the results of the multiple linear regression obtained a relationship of 0.656, it can be concluded that the activity of playing online games together has a strong and significant effect on moral and students’ study motivation of SMA Negeri in Kabupaten Penajam Paser Utara.